Migration and Differential Labour Market Participation: Theoretical Directions, Recurring Themes, Implications of Brexit and Areas for Future Research. Issue 4 (13th June 2017) - Netto, Gina; Craig, Gary
Abstract : Extensive research in a number of disciplines, including economics, social policy, sociology, geography and management have been undertaken relating to migrant participation in the labour market. Given the highly topical nature of migrant employment in Western Europe and the US, the aim of this brief review is to draw together some of the more recent attempts to theorise on the presence of migrants in the labour market, discuss some of the recurrent themes that have emerged from empirical research in this area, consider some of the main implications for policy-making in what now seems likely to be known as the post-Brexit era and outline areas for future research. In doing so, the intention is to contribute to further inter-disciplinary theory-building and to a more nuanced understanding of the complexity of this highly politicised area and the implications of migrant employment for policy and future research.